Peran Penerapan E-Government Terhadap Peningkatan Kinerja Pelayanan Publik pada Instansi Pemerintah - Hendrian, Hendrian; Suparno, Suparno; Wahono, Puji; Handaru, Agung Wahyu (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The goal to be achieved in this study emphasizes the role of the application of e-government on the performance of public services in government agencies. The method used in this study is literature research using secondary data in the form of books and related journals. The main source of data for this research is scientific articles published in various journals and indexed by google scholar. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of this research show that human resources are needed who have adequate competencies on top of technological developments so that implementing E-Government will be easier. Furthermore, it is necessary to have a budget and maximum facilities and infrastructure which can help government workers in providing services. The government must develop e-government, in which there must be channels that are able to answer the challenges of technological developments so that officials can easily adapt to existing developments.